An exploration of factors associated with food protein‐induced enterocolitis syndrome: Birth, infant feeding and food triggers. Issue 4 (22nd January 2021) - Lee, Eric; Barnes, Elizabeth H.; Mehr, Sam; Campbell, Dianne E.
Abstract: Background: Food protein‐induced enterocolitis syndrome (FPIES) is a non–IgE‐mediated food allergic disorder with a well‐characterized phenotype, but limited understanding of factors associated with food cross‐reactivity, severity and tolerance. Methods: A retrospective cohort study spanning 20 years on children with acute FPIES from a single paediatric tertiary centre in New South Wales, Australia, focusing on identifying food trigger co‐associations and factors associated with reaction severity, multiple trigger FPIES and/or tolerance was performed. Results: A total of 168 individuals with 329 recorded FPIES episodes between 1997 and 2017 were included. 49% were male. The median age at first reaction was 5 months, and median age at diagnosis was 9 months. 73% experienced at least one severe FPIES reaction. Rice (45%), cow's milk (30%) and soya (13%) were the most common triggers. Rice or cow's milk FPIES was strongly associated with increased odds of having multiple trigger FPIES. The odds of having multiple food FPIES and severe reactions were slightly decreased with vaginal delivery. No factors were associated with increased risk of severe reactions. Infants with rice and grains FPIES outgrew their reactions at an earlier age, compared to those with fish FPIES. Conclusions: Rice remains the most common trigger in Australia with co‐associations between rice/oats and cow's milk/soya observed. This suggests that taxonomically related foods may share similar protein structure and trigger similar mechanisms of antigen recognition. Vaginal delivery may have a mild protective effect on the development of multiple FPIES and severe reactions. No other features from birth or infant‐feeding history influenced outcomes in FPIES.